Trilogi Wacana Citra Anggota Legislatif PKS di Instagram: Analisis Kritis Komunikasi Politik, Dakwah, dan Personal Branding pada Akun Instagram @endah_purwnti: Studi Kasus Kota Bogor - Dwi Muliati; Dewi Anggrayni (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to deconstruct the image construction of a Prosperous Justice Party (PKS) legislator in the digital realm, focusing on how narratives of political communication, da'wah missions, and personal branding are interwoven into a unified discourse. Employing a qualitative method with a case study approach reinforced by an in-depth literature review, this research analyzes the content of the Instagram account @endahpurwnti, a member of the Bogor City Council. Data analysis techniques utilize Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) model to dissect the dimensions of text, discursive practice, and sociocultural practice. The results indicate the existence of a mutually reinforcing "Discourse Trilogy": (1) Advocacy/Political Discourse, which represents the politician as a solution-oriented "servant of the people" through content regarding constituency visits (reses) and aspiration gathering; (2) Da'wah Discourse, which frames political activity as worship (amar ma’ruf nahi munkar) through the use of religious diction and syar’i visual symbols; and (3) Personal Branding Discourse, which displays a humanist, friendly, and egalitarian side to build emotional proximity. These findings confirm that for PKS politicians, Instagram is not merely a political showcase, but a modern da'wah pulpit that blurs the boundaries between the identities of a politician, a preacher, and a public figure relatable to urban voters. This study contributes to the understanding of identity hybridization strategies in contemporary Islamic political communication in the digital era.